2021
DOI: 10.3389/fneur.2021.673816
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Influences in Parkinson's Disease Patients and Their Caregivers: Perspectives From an Australian Cohort

Abstract: Objectives: Cognitive impairment impacts negatively on Parkinson's disease (PD) patient and caregiver quality of life (QoL). We examined cognitive impairment in PD patients and their caregivers to determine if caregiver cognition affected their PD relative.Methods: Validated cognition and clinical outcome measures were assessed in 103 PD patients and 81 caregivers.Results: PD patients showed more cognitive impairment than their carers, with 48.6% having possible Mild Cognitive Impairment (MCI) and 16.5% having… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Briefly, 56.3% of the PD participants were male with a mean age of 67.1 years (range 35–88, standard deviation [SD 12.2]), whilst two thirds of the HCs were female, with a mean age of 62.4 years (range 18–90, [SD 15.6], p = 0.001). All relevant demographic, clinical parameter and nutritional intake information has been reported previously for this cohort ( Lubomski et al, 2020a , b , 2021a , b ; Palavra et al, 2021 ) and is reproduced in Tables 1 , 2 and Supplementary Data , where relevant to this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, 56.3% of the PD participants were male with a mean age of 67.1 years (range 35–88, standard deviation [SD 12.2]), whilst two thirds of the HCs were female, with a mean age of 62.4 years (range 18–90, [SD 15.6], p = 0.001). All relevant demographic, clinical parameter and nutritional intake information has been reported previously for this cohort ( Lubomski et al, 2020a , b , 2021a , b ; Palavra et al, 2021 ) and is reproduced in Tables 1 , 2 and Supplementary Data , where relevant to this study.…”
Section: Resultsmentioning
confidence: 99%
“…Information regarding socio-demographic factors, lifestyle, clinical management and comorbidities was collected from validated surveys, as previously reported ( Lubomski et al, 2020a , b , 2021a , b , 2021c ; Palavra et al, 2021 ). A comprehensive Food Frequency Questionnaire ( Barclay et al, 2008 ), was completed by all participants.…”
Section: Methodsmentioning
confidence: 99%
“…Subjects were recruited from the movement disorder and neurology clinics at Royal North Shore Hospital, Sydney, Australia, as reported in our previous studies ( Lubomski et al, 2020a , b , 2021a , b , c ; 2022 ). Inclusion criteria: being managed by a specialist neurologist, a clinical diagnosis of idiopathic PD according to the UK Parkinson’s Disease Society Brain Bank Diagnostic Criteria ( Hughes et al, 1992 ), and >18 years of age.…”
Section: Methodsmentioning
confidence: 99%
“…Another caregiver measure that was evaluated was caregiver strain ( n = 6). All six studies identified a significant relationship between caregiver strain and PD QOL (summary of association = 100%) 38,48‐58 . In these studies, higher caregiver strain was associated with worse QOL for the PD patient.…”
Section: Resultsmentioning
confidence: 95%
“…All six studies identified a significant relationship between caregiver strain and PD QOL (summary of association = 100%). 38,[48][49][50][51][52][53][54][55][56][57][58] In these studies, higher caregiver strain was associated with worse QOL for the PD patient. Most articles examined this relationship with univariable analyses; however, one article did report the results of a regression analysis that accounted for patient sex, age, comorbidities, Hoehn and Yahr stage, mobility, verbal fluency, recall scores, and the use of treatments for depression, psychosis, and cognition.…”
Section: Caregiver Strainmentioning
confidence: 99%